Root-released organic anions in response to low phosphorus availability: recent progress, challenges and future perspectives - Wang, Yanliang; Lambers, Hans (Plant and soil, 2020)
Background To improve plant phosphorus (P)-acquisition efficiency to secure sustainable food production, an important step is to increase the concentration of plant-available P in the rhizosphere. Root exudation of organic anions is a key strategy in mobilizing less-available soil P. Scope This review covers how organic anions (carboxylates) mobilize soil P and research methodologies applied. It then discusses the root-release of organic anions induced by low P availability and their contribution to soil P mobilization and plant P acquisition, and highlights the impact, challenges and perspectives in this research area. Conclusions The release of organic anions is increased considerably in some plant species, but very little in others under low P availability. Rhizosphere organic anions play important roles in increasing plant-available P, but the contribution is greatly affected by many factors. In future research, improved and ecologically meaningful root exudation sampling methods, the use of mature leaf manganese (Mn) concentration or total 14 C exudation as a proxy for rhizosphere carboxylates, case-by-case field experiments, molecular mechanisms underpinning organic anion biosynthesis and efflux under low P availability warrant further attention. Finally, carbon costs and multiple root trait combinations (e.g., root hairs plus root exudation) should be considered in crop breeding programs to generate more P-efficient cultivars.